FAKTOR INFRASTRUKTUR DALAM PEMBANGUNAN EKONOMI KOTA MATARAM - SANTIAN, SANTIAN; KARISMAWAN, PUTU; SARIPTA W.M, BAIQ (GANEC SWARA, 2019)
This study is entitled "Infrastructure Factors in the Economic Development of the City of Mataram". The purpose of this study is to look at the role of road infrastructure, electricity infrastructure and education infrastructure, both partially and simultaneously in the economic development of the City of Mataram. Infrastructure indicators in this study include roads, electricity and education. Gross Regional Domestic Product (GRDP) on the basis of being used as an economic indicator. Infrastructure data and GRDP analyzed cover the period 2001-2016.   The results of the analysis show that simultaneous road, electricity and education infrastructure play a significant role in the economic development of the city of Mataram. partially road infrastructure and electricity infrastructure play a significant role in the economic development of the City of Mataram.